Ground penetrating radar processing in producing 3D visualization of subsurface utility mapping - Nadiah Ismail, 1986-; Zainal Abidin Md. Som, supervisor; Fakulti Geoinformasi dan Harta Tanah (2009)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2009